2020
DOI: 10.1101/2020.07.08.20148866
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Predictors of Anxiety Regarding The COVID-19 Pandemic Among Health-care Workers in a Hospital Not Assigned to Manage COVID-19 Patients in Nepal

Abstract: Introduction: We studied the levels and severity of anxiety caused by COVID-19 amongst frontline health-care workers (HCWs) in a tertiary care neurological hospital in Nepal, not assigned to manage COVID-19 cases. Methods: A cross-sectional study was conducted on 100 frontline Health Care Workers (HCWs) using a 10-point subjective assessment tool, the Anxiety Level Index (ALI), and the Zung Self Rating Anxiety Score (SAS), to assess the level of anxiety regarding COVID-19. Results: On ALI 55% of HCWs w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 28 publications
2
2
0
Order By: Relevance
“…Our study revealed that adverse psychological symptoms (stress, depression and anxiety) had been recorded in almost one third to one half of respondents, while insomnia had been recorded in more than half. Similar results were found in other studies addressing psychological outcomes in health-care professionals (15,16). The majority of health-care professionals considered the COVID-19 pandemic to be under control in Egypt.…”
Section: Adverse Psychological Symptoms and Insomniasupporting
confidence: 88%
See 1 more Smart Citation
“…Our study revealed that adverse psychological symptoms (stress, depression and anxiety) had been recorded in almost one third to one half of respondents, while insomnia had been recorded in more than half. Similar results were found in other studies addressing psychological outcomes in health-care professionals (15,16). The majority of health-care professionals considered the COVID-19 pandemic to be under control in Egypt.…”
Section: Adverse Psychological Symptoms and Insomniasupporting
confidence: 88%
“…Female gender could also significantly predict experiences of stress and anxiety when compared to males in the groups. Similarly, previous studies among health-care professionals have indicated that females are at a higher risk of developing anxiety and depression in such situations (16,19). Our study showed that younger health-care professionals were more likely to report stress, depression and anxiety compared to older health-care professionals.…”
Section: Associated Factorssupporting
confidence: 84%
“…(2020) [65] Serbia (2020) [71] Nepal 100 NR 26.8 ± 8.17 Vafaei, H. (2020) [72] Iran Zhu, J. (2020) [82] China 165 (100) The results of the subgroup analysis are presented in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…26 Length of working time and the frequency of checking for COVID-19 related information were significant predictors of anxiety. 27 Special training on the use and management of personal protective equipment and handling COVID-19 patient could reduce anxiety. 28 That could help and support them to work effectively decreases the psychological stress and anxiety which improve the mental health of Health Care Worker.…”
Section: Discussionmentioning
confidence: 99%